Relationship between Energy Consumption, Foreign Direct Investment, and Labor Force Participation Using the VECM Model: Empirical Study in OECD Countries - Wahyudi, Heru; Palupi, Widia Anggi (International Journal of Energy Economics and Policy, 2023)
The purpose of this study is to determine the causal relationship as well as the long-term and short-term relationship between total energy consumption, foreign direct investment (FDI), and labor force participation rates in OECD countries from 1994 to 2019 using Granger Causality Test and Vector Error Correction Model (VCEM). In this study, it is found that energy consumption and FDI have a two-way causality, energy consumption and the labor force participation rate have a two-way causality and FDI and the labor force participation rate have a two-way causality. In the long term, FDI has a significant positive effect on energy consumption while labor force participation has an insignificant negative effect on energy consumption. Meanwhile, in the short term, FDI and labor force participation rates have no effect. This research contributes to decision-making in the field of energy, FDI, and improving the quality and quantity of the workforce in OECD countries.